Where is communication breaking down? Narrative tensions in obesity-in-pregnancy clinical encounters. - Rachel Dadouch; Sarenna Lalani; Rory Windrim; Cynthia Maxwell; John Kingdom; Rohan D'Souza; Janet Parsons (PLoS ONE)
There are numerous biomedical and psychosocial challenges associated with obesity in pregnancy that impede communication between healthcare providers (HCPs) and patients. We conducted a narrative study informed by stigma theory to understand specific areas of communication breakdown in obesity-in-pregnancy clinical encounters. Sixteen patients and 19 HCPs participated in in-depth, semi-structured interviews. We explored how participants positioned obesity-in-pregnancy clinical encounters within their broader narratives. Employing narrative analysis, we identified five narrative tensions contributing to communication challenges: 1) obesity as a detriment to health versus an acceptable biologic variation; 2) obesity as the result of personal choice versus the result of uncontrollable circumstances; 3) a regular pregnancy versus a high-risk diagnosis; 4) a typical and problem-free clinical encounter versus a tremendously difficult clinical encounter; and 5) talking openly about Body Mass Index (BMI) and related co-morbidities versus sidestepping the topic. How participants positioned themselves relative to prevailing societal discourses regarding obesity in general influenced these tensions. These narrative tensions revealed specific areas where communication is vulnerable to breaking down during the obesity-in-pregnancy clinical encounter. Participants' (both HCPs and patients) past experiences of clinical encounters-and the meanings they ascribe to them-shape subsequent encounters, and our analysis illuminates the complexities of this interactive space. This research has implications for improving clinical practice and education.